Pemanfaatan Media Multimodal dalam Pembelajaran Keterampilan Membaca Teks Berita - Asra Fania; Syahrul Ramadhan (STIKes Ibnu Sina Ajibarang, 2026)
This study aims to describe the utilization of multimodal media in teaching news text reading skills among seventh-grade junior high school students. The research employed a quantitative approach with a descriptive research design. The data were collected through questionnaires distributed to 61 seventh-grade students as the research respondents. The research instrument used a Likert scale covering aspects of students’ perceptions, comprehension, motivation, participation, and readiness toward the use of multimodal media in learning news text reading skills. The data were analyzed using descriptive quantitative techniques through percentage calculations and interpretation of respondents’ answers. The findings revealed that most students showed positive responses toward the use of multimodal media. A total of 72.1% of students agreed that learning through printed and digital media made the learning process more engaging. In addition, 59% of students stated that digital media helped them understand news content more clearly, while 60.7% felt more active during learning activities using multimodal media. The use of multimodal media also increased students’ motivation, self-confidence, and reading comprehension skills in understanding news texts. The findings indicate that the combination of printed and digital media creates a more interactive and effective learning environment that aligns with students’ literacy needs in the digital era. Therefore, multimodal media can serve as an alternative instructional strategy to improve students’ news text reading skills in junior high schools. The implications of this study highlight the importance of integrating digital and printed media in Indonesian language learning to enhance students’ reading literacy quality.